Amphiphilic polymeric nanoreactors containing Rh(i)–NHC complexes for the aqueous biphasic hydrogenation of alkenes. Issue 20 (14th September 2021) - Sambou, Sasaline Salomon; Hromov, Roman; Ruzhylo, Illia; Wang, Hui; Allandrieu, Audrey; Sabatier, Cassandra; Coppel, Yannick; Daran, Jean-Claude; Gayet, Florence; Labande, Agnès; Manoury, Eric; Poli, Rinaldo
Abstract : A rhodium(i ) complex bearing a monodentate N-heterocyclic carbene ligand has been confined into the core of amphiphilic core-crosslinked micelles (CCMs). Abstract : A rhodium(i ) complex bearing a monodentate N-heterocyclic carbene ligand has been confined into the core of amphiphilic polymeric core-crosslinked micelles (CCMs). The Rh complex was covalently bound to the polymeric chains by incorporation of a polymerizable unit on the NHC ligand. Nanoreactor Rh–NHC mes @CCM 5b has been evaluated as a catalyst for the aqueous biphasic hydrogenation of styrene and other alkenes. It has shown a high activity with styrene at a low catalytic loading (10 000/1 substrate/Rh ratio), greater than that of an analogous molecular Rh(i ) complex, and its evolution to Rh 0 is slower. This is attributed to several factors, among which the confinement effect and the favourable polyoxygenated environment of the nanoreactor core. Finally, the CCMs could be recycled up to four times with almost no loss of activity over 3 h cycles and the loss of rhodium per cycle was on average lower than 0.6 ppm.